Bright future or blind alley? CAR-T cell therapy for solid tumors - Zhang, Kai; Chen, Hong; Li, Fuqiang; Huang, Sheng; Chen, Fei; Li, Yi (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) T cells therapy has emerged as a significant breakthrough in adoptive immunotherapy for hematological malignancies with FDA approval. However, the application of CAR-T cell therapy in solid tumors remains challenging, mostly due to lack of suitable CAR-T target antigens, insufficient trafficking and extravasation to tumor sites, and limited CAR-T survival in the hostile tumor microenvironment (TME). Herein, we reviewed the development of CARs and the clinical trials in solid tumors. Meanwhile, a “key-and-lock” relationship was used to describe the recognition of tumor antigen via CAR T cells. Some strategies, including dual-targets and receptor system switches or filter, have been explored to help CAR T cells matching targets specifically and to minimize on-target/off-tumor toxicities in normal tissues. Furthermore, the complex TME restricts CAT T cells activity through dense extracellular matrix, suppressive immune cells and cytokines. Recent innovations in engineered CARs to shield the inhibitory signaling molecules were also discussed, which efficiently promote CAR T functions in terms of expansion and survival to overcome the hurdles in the TME of solid tumors.